Gender, migration, remittances: evidence from Germany - Elke Holst; Andrea Schäfer; Mechthild Schrooten (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
Gender-specific determinants of remittances are the subject of this study based on German SOEP data (2001-2006). In 2007, about 7.3 million foreigners were living in Germany. While the total number of foreigners has decreased over the last decade, female migration to Germany has increased. Today, women constitute 48.6% of migratory flows to Germany, although the proportion varies significantly by country of origin. A feminization of migration is observable all over the world, and is changing gender roles in the households of origin as well. To date, research has failed to address the gender-specific determinants of remittances from Germany. Here we attempt to fill this gap, focusing on gender roles and network effects. We distinguish between three different groups of migrants: foreigners, Germans with migration background, and all individuals with personal migration experience. Our main findings show, above all, that gender matters. However, the gender differences identified disappear after controlling for transnational (family) networks. Taking interaction terms into account reveals gender-specific network effects. In addition, different groups of migrants show remarkable differences in international networking. We find that female foreigners, but not female migrants with German citizenship, remit less than males if their children live abroad. Female migrants with German citizenship send more money home if their siblings remain in the home country. The reverse is true in the case of female migrants with foreign citizenship. Our findings show that female migrants tend to support their children first and foremost, while male migrants tend to support a wider network of more distant family members and friends. This finding is in sharp contrast to previous studies on remittances. It makes clear that there is little evidence supporting the assumption that remittances simply follow income-difference based altruism or that women are more altruistic than men. Furthermore, there seems to be evidence that the gender-specific differences detected in remittance behaviour might be due to gender-specific migration patterns and the relative role of the migrant within the transnational network.
Keywords: F24; J16; D13; 330; Remittances; economics of gender; immigrant workers; Rücküberweisung (Migranten); Migranten; Geschlecht; Soziales Netzwerk; Frauenerwerbstätigkeit; Deutschland